Media Literacy and Moral Panic in the Acehnese Community’s Response to Rohingya Refugees: A Qualitative Case Study on the Implications of Critical Education - Salbiah, Rahma; Yudasril, Yudasril; Aufa, Nauwal; Al Ansari, Khabin; Wahyuni, Intan; Jannah, Miftahul (Global Educational Research Review, 2025)
Purpose –  This study aims to explore the interrelation between media literacy, moral panic, and the Acehnese community’s response to Rohingya refugees. Although the issue of Rohingya refugees has previously been examined from legal, social, and cultural perspectives, the role of media literacy—particularly within educational contexts—remains underexplored. This study is significant due to the widespread dissemination of hoaxes, such as claims that “Rohingya refugees are a diversion from the Palestine issue” and demands for “permanent resettlement,” which have substantially influenced local public perceptions.. Methods/Design/Approach – This research employs a qualitative method with a case study approach in Aceh, Indonesia. Data were collected through in-depth interviews with 20 key participants, including local community members, Rohingya refugees, and practitioners in education and media; participatory observation; document analysis of media and international organizational reports; and Focus Group Discussions (FGDs). Data analysis was conducted using a thematic approach and verified through source and method triangulation. Findings – he findings reveal that the initial solidarity of the Acehnese community toward Rohingya refugees was shaped by local values and maritime customary law in the absence of formal state regulations. However, this positive perception shifted significantly due to the spread of hoaxes via social media, triggering moral panic, social segregation, political tensions, and collective acts of rejection against the refugees. The majority of respondents emphasized the need to integrate media literacy into both formal and informal educational systems to mitigate these negative impacts. Originality/Value – This study makes a theoretical contribution by explicitly integrating the concept of critical media literacy into the analysis of moral panic surrounding the Rohingya refugee issue, an area previously underexplored in the literature. It also specifically documents the role of hoaxes in shaping public perception, offering new insights into the interaction between media literacy, moral panic, and social responses within the context of refugee crises. Practical Implications – Practically, the findings recommend implementing critical media literacy within formal and informal education curricula, particularly at senior high schools and Islamic boarding schools (pesantren). In addition, community-based media literacy programs involving local leaders, as well as the synchronization of policies between central and regional governments, are crucial for enhancing critical awareness and social empathy in addressing global refugee challenges. Limitations – This study is limited to the geographical context of Aceh and faced linguistic constraints during interviews with Rohingya refugees, which may affect the generalizability and depth of the findings. Keywords Media literacy, moral panic, Rohingya refugees, critical education, Aceh Paper type Research paper